Amygdalin laetrile-a nascent vitamin B17: a review - Bora, Aparajeeta; Silvia C. R., Wilma Delphine; Mohanty, Shrabani; Pinnelli, Venkata Bharat Kumar (International Journal of Research in Medical Sciences, 2021)
Amygdalin is also called Vitamin B17 and its semi synthetic product is laetrile. It is a natural glycoside nutrient which gained popularity due to wide availability and low cost in treating various diseases. Vitamin B17 is derived from natural food sources and can be used for cancer prevention in alternative medicine practices. This review illustrates the proposed anticancer activity and other effects of amygdalin on different body systems along with a variety of clinical trials on humans and animals with pharmacological, toxicological effects and provides a perspective for further investigation and research.